A Conceptual Framework Encompassing the Psychoneuroimmunoendocrinological Influences of Listening to Music in Patients With Heart Failure. Issue 2 (March 2018) - Burrai, Francesco; Hasan, Wohaib; Luppi, Marco; Micheluzzi, Valentina
Abstract : Patients with heart failure have been traditionally treated with a pharmacology-based approach, diet, exercise, and rehabilitation for reducing symptoms, hospitalizations, and mortality. We have developed a solid conceptual framework for music listening–based protocols, showing how music may have a broad range of positive effects on cardiovascular health through psychoneuroimmunoendocrinological pathways.